Evaluation of Tomato Cultivars against Early Leaf Blight (Alternaria solani) in net greenhouse Qatar (JOURNAL OF ADVANCES IN AGRICULTURE, 2023)
The current study was conducted at the Alutouriya research station under the Agriculture Research Department in the Ministry of Municipality, Qatar, during the years 2020–2021, and 2021–2022, to test the response of various tomato cultivars against early blight. Early blight is the most devastating fungal disease of tomatoes, caused by Alternaria solani. It is one of the most common foliar diseases in tomatoes. The disease can occur in a wide range of climatic conditions but is most prominent in areas with moderate temperatures and high relative humidity. In this study, ten tomato cultivars were evaluated for highly resistant (HR), resistant (R), moderately resistant (MR), moderately susceptible (MS), and susceptible (S) reactions under natural net greenhouse conditions. Alternaria solani produces oblivious green, gray, and brown-to-black colonies when grown on PDA medium. Assessments on the mean percent disease index and severity grade of symptoms were recorded for each cultivar. Only one cultivar, 71 (banana legs), was recorded as moderately susceptible in both years with a high PDI value and symptom severity grade. The cultivars fruit weight for each cultivar was calculated to determine the productivity of the tomato plant. The maximum and minimum temperatures with relative humidity were recorded every week from November to February for the years 2022-2021 and 2021-2020. This data revealed that most of the cultivars used for this study were resistant to early blight.